The effect of dose on the intensity of dependence in morphine-dependent mice - Jusoh, Ahmad Jamaluddin Al-Qasami; Syd Mohmad Faudzi, Syed Mohd Syahmi; Suhaimi, Maryam Saadah; Hashim, Ridzwan; Ridzwan, Irna Elina (2015)
Introduction: Animal behaviour research is an important tool to study the addiction properties of addictive substances. The Conditioned Place Preference (CPP)paradigm is among the model used to achieve this purpose. It can be used to investigate a wide range of addiction related behaviour including intoxication and relapse potential. Since it involves a long cycle experiment, it is important to optimise the experimental conditions, but minimising any unnecessity. Therefore, in this study we aim to investigate the effects of different morphine dose (3.75 - 10 mg/kg) towards intensity of morphine dependence in adult Swiss albino mice.